How to Cheat and Not Feel Guilty: Cognitive Dissonance and its Amelioration in the Domain of Academic Dishonesty. Issue 2 (3rd April 2017) - Stephens, Jason M.
Abstract : The belief that cheating is wrong doesn't prevent its enactment. For example, many students cheat despite believing that is wrong or unjustifiable. The question taken up in this article concerns how the resulting cognitive dissonance is ameliorated; that is, how do students cheat and not feel guilty? This article will describe two "good" theories that offer some insight into the psychological and social processes underlying the reduction of cognitive dissonance. Specifically, attribution theory and social norms theory serve as conceptual lenses for understanding how students manage cognitive dissonance related to academic dishonesty. Finally, in the spirit of Kurt Lewin, these two "good" theories are discussed in terms of the design and development of "wise interventions" aimed at promoting academic integrity and reducing the prevalence of cheating.